2016
DOI: 10.1128/msphere.00350-16
|View full text |Cite
|
Sign up to set email alerts
|

Species in the Cryptococcus gattii Complex Differ in Capsule and Cell Size following Growth under Capsule-Inducing Conditions

Abstract: Infections with the fungal pathogen Cryptococcus gattii have been increasing in recent years. Recently, four different species have been described within C. gattii, which correspond to four previously known molecular genotypes (VGI to VGIV). Examining traits related to infection and disease is important for determining whether these different species have clinical relevance. This study examined variation in attributes that are important for infecting and surviving in the host, including tolerance to various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 60 publications
3
41
0
Order By: Relevance
“…4B). These observations were consistent with those of previous work that showed that VGI molecular type strains have larger capsules (26). NLE in C. neoformans-and C. gattii-infected macrophages.…”
Section: Resultssupporting
confidence: 93%
“…4B). These observations were consistent with those of previous work that showed that VGI molecular type strains have larger capsules (26). NLE in C. neoformans-and C. gattii-infected macrophages.…”
Section: Resultssupporting
confidence: 93%
“…Analysis of the signalling networks responsible for the increased thermotolerance of the SCH9 protein kinase mutant identified the heat shock transcription factor HSF1 to have both transcriptional repressing and activating activities with thermal stress [32]. Interestingly, C. gattii strains exhibit reduced thermotolerance in comparison to C. neoformans, apart from the VGII group containing the Vancouver Outbreak strains [33]. However, environmental VGII C. gatti growth in Vancouver Island was positively correlated with temperate conditions [34].…”
Section: Surviving the Warm-blooded Hostmentioning
confidence: 99%
“…The isolate grew and produced blue pigment on CGB agar which is unique to C. gattii species (Figure 3A) (30). Cryptococcus produces a hydrophilic extracellular capsule as a means of evading the host immune system (31). To analyze capsule production, India ink staining and microscopic evaluation was performed after growth in CO 2 -independent medium for 72 hours at 37°C.…”
Section: Resultsmentioning
confidence: 99%